MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) DI DESA ILOHELUMA KABUPATEN GORONTALO MELALUI PROGRAM KKM - Sucia Pratiwi Tampoy; Radhitya Nur Rahman Pakudu; Sriyani Paradila Mohamad; Delpi Ibrahim; Clara Pratiwi Botutihe; Naya Aurelia Bilondatu; Aurelia Ciquita Putri Lahema; Irnawati Kabutu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is an effort to implement programs directly related to the Sustainable Development Goals (SDGs) at the village level through the Independent Work Study Program (KKM) involving students. The research method uses a descriptive qualitative approach with interviews and observations as data collection techniques. This research was conducted in Iloheluma village, Boliyohuto sub-district, Gorontalo district. The results of this study show that the implementation of SDGs in this village includes quality education, decent work and economic growth, digitization of MSMEs (Micro, Small and Medium Enterprises), and anti-bullying campaigns. Collaboration between KKM students, the village government, the local community, and schools is important in the application of knowledge and is the key to success in achieving sustainable goals at the local level.